Initiating Dialogues, Breaking Silences: Strategies for Redressing Historical Traumas - Sigdel, Keshab (Literary Studies, 2015)
Historical traumas are carried forward into the present in the psyche and life not only of those who experienced the trauma directly, but also to the generations that follow. And in many cases, silence has been an important carrier of this unspeakable past. Revisiting the past becomes an effective strategy of interaction and dialogue in order to reconcile with the historical trauma. I discuss two texts which deal with the depiction of historical violence and the resulting trauma—Tara Rai’s Chhapamar Yuvati ko Dayari (Diary of a Guerilla Girl) and Khuswant Singh’s Train to Pakistan—and attempt to see how recovering memories of the past, as psychologist Ramsay Lieum claims, can contribute not only to understanding the lasting psychological impacts of intense social and political conflicts but also exploring prospects for personal and social reconciliation.